Comparative efficacy and safety of rimegepant, ubrogepant, and lasmiditan for acute treatment of migraine: a network meta-analysis. (2nd January 2022) - Johnston, Karissa; Popoff, Evan; Deighton, Alison; Dabirvaziri, Parisa; Harris, Linda; Thiry, Alexandra; Croop, Robert; Coric, Vladimir; L'Italien, Gilbert; Moren, James
ABSTRACT: Objective: In the absence of head-to-head comparisons, the objective of this study was to conduct a network meta-analysis (NMA) to indirectly compare the relative efficacy and safety of rimegepant, ubrogepant, and lasmiditan for the acute treatment of migraine. Methods: A systematic literature review was conducted to identify randomized controlled trials (RCTs) of rimegepant, ubrogepant, and lasmiditan in adults with acute migraine. Outcomes included sustained pain freedom and -relief 2–48 hours post-dose, and adverse events. No RCTs were identified that directly compared these interventions. Therefore, a fixed-effects Bayesian NMA was conducted by identifying a connected (via comparison to placebo) network of RCTs. Results: Five RCTs were identified as follows: rimegepant study 303 (n = 1, 466), ubrogepant ACHIEVE I and II (n = 1, 672 and n = 1, 686, respectively), and lasmiditan SAMURAI and SPARTAN (n = 2, 231 and n = 3, 005, respectively). Efficacy outcomes (pain freedom and relief at 2, 24, 48 hours) tended to be highest for lasmiditan 200 mg and rimegepant followed lower doses of lasmiditan and all doses of ubrogepant. However, lasmiditan 200 mg was also associated with higher rates of adverse events, particularly somnolence and dizziness. Conclusions: Lasmiditan, rimegepant, and ubrogepant all performed significantly better than placebo with respect to pain freedom and pain relief. Efficacy results were similar for rimegepant and lasmiditan with rimegepant having higher rates of pain freedom and relief than lower doses of lasmiditan, while somnolence and dizziness outcomes were lower for rimegepant than higher doses of lasmiditan.